The digital divide in rural Ethiopia: Determinants and implications of sex-disaggregated mobile phone ownership and use - Warner, James; Marilign, Yalew M.; Habte, Yetimwork (International Food Policy Research Institute, 2023)
Mobile phones are rapidly being adopted in less developed countries, with widely acknowledged commensurate socio-economic benefits, including United Nations SDGs advocating for increased ownership of mobile phones to promote women’s empowerment. While overall mobile phone ownership is rising quickly in Ethiopia, it is lagging for rural women, particularly married rural women. Overall, we find that married men are approximately five times more likely to own a phone than their wives even though married women with phones are more active in agricultural decision making. This lack of female mobile phone ownership should be considered within the broader context of several recent Ethiopian digital initiatives, including mobile banking and mobile payments. These initiatives are likely to provide greater benefits to those individuals that own a mobile phone. By applying gender analysis to phone ownership, we believe that we can anticipate some potentially unexpected negative consequences for women created by these mobile phone initiatives. This paper outlines current rural sex-disaggregated phone ownership trends, determinants of phone ownership, and related impacts on intrahousehold decision making. We believe that by identifying these gender differences in mobile phone ownership, policymakers can better target their digital economy initiatives.